Development of Digital Teaching Documents Based on Problem Based Learning to Improve Students' Science Process Skills on Mammal Class Material - Sugeng Mashabhi; Shanty Savitri; Elga Araina; Ririn Fahrina (Scientiae Educatia: Jurnal Pendidikan Sains, 2023)
21st century learning prepares a generation that welcomes information and communication technology (ICT) advances in social life and triggers technological developments so that it can open up great potential for changes in the way of learning and obtaining information. Such learning requires specially designed teaching materials to support the process in order to create maximum learning outcomes. This study aims to develop teaching materials to improve students' Science Process Skills (SPS) on mammalian class material. This research uses the R&D method with the ADDIE research model. Data collection techniques used interviews, validation, response questionnaires, SPS observations, and tests. Data from validation and response questionnaires were analyzed using the eligibility criteria formula and respondent criteria. The data of SPS improvement was analyzed by N-Gain test. The results showed that this study produced teaching material consisting of teaching materials, lesson plan, student worksheet, and practicum guides in digital form that were suiTable for use. This is based on the acquisition of material, media and learning expert assessments, and linguists of 80%, 80%, and 91% as well as student responses with an average score of 4.3. In addition, the increase in SPS in the control and experimental classes with an average score of 0.45 and 0.62 is included in the medium criteria and observation of SPS from 6 indicators gets a high category in the experimental class while the control class only gets 1. Based on these results, the PBL-based digital teaching material is feasible, effective, and can improve student SPS.